Design and Construction of a Transaction System for the Manggis Mandiri Building Store in Teluk Kuantan - Wilma Tiana; Helpi Nopriandi (Universitas Islam Kuantan Singingi, 2023)
Currently, the use of computers is very much needed in the process of processing data into information needed by companies. By implementing a computerized system in a company, it is considered to really help the company in making decisions based on the information produced by the system. The Manggis Mandiri Building Shop is a building shop that is currently developing and operates in the sales of building materials, where data processing of goods and receivables is still done manually and all activity reports on the bookkeeping system are still poorly structured. The obstacles that arise are the time problem where calculating receivables or checking goods data takes too long and also the problem of controlling the stock of available goods which is not very well organized. Therefore, the author designed a web-based application using Php Mysql, Xampp and the Laravel Framework. The source of data obtained is through primary data sources and data collection techniques are carried out by means of observation, interviews and documentation. It is hoped that this system can make it easier for Manggis Mandiri stores to run their business and gain profits amidst a lot of competition. As a result of the research, this application has met the system requirements needed such as recording receivables, stock of goods, reporting goods in and goods out.